Penerapan Metode TANDUR berbantuan Model Buzz Group untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran Fiqih Kelas VIII MTsN 11 di Jombang - Hidayah, Khoirur Rosyidatul; Chotimah, Chusnul (YASIN, 2025)
The low level of students' understanding of Fiqih in Grade VIII at MTsN 11 Jombang is the primary issue addressed in this study. This issue is influenced by internal factors such as differences in intelligence, as well as external factors including out-of-school habits that affect learning concentration. The objective of this research is to examine the implementation of the TANDUR method, supported by the Buzz Group model, in enhancing students' comprehension, and to evaluate the impact of its application. A qualitative approach was employed using a case study method, with data collected through observation, interviews, questionnaires, and documentation. The findings indicate that the implementation of the TANDUR method which includes the stages of Tumbuhkan, Alami, Namai, Demonstrasi, Ulangi, and Rayakan, combined with small-group discussions (Buzz Group), significantly improved students’ conceptual understanding of Fiqih. The learning process became more active, collaborative, and engaging, encouraging students to think critically, express ideas, and engage in interactive learning with their peers. The study concludes that the TANDUR method, assisted by the Buzz Group model, is effective in improving the quality of Fiqih instruction. Its implication suggests that this approach can be adopted by Islamic education teachers as an innovative and collaborative strategy aligned with the characteristics and learning needs of today’s students in the madrasah context.